Simple colour design, and colour in LaTeX2ε - Goossens, M; Rahtz, S (TeX Users Group, 1994)
This article reviews some basic principles underlying the use of colour. We start by a review of the functional use of colour, explaining how it can help to focus attention, explain relationships, guide the viewer/reader through the presented information so that its contents is easier to absorb and appreciate. Some common rules for optimizing communication using colour elements in documents are discussed. We then explain the colour support in LaTeX2ε and give some examples.